Relevance of Supplyco and its Operations in Kerala’s Current Scenario - Deepthi Mary Mathew and Nimmish Sany
Kerala State Civil Supplies Corporation, otherwise known as Supplyco, is a household name across Kerala. Supplyco was formed in 1974 with the primary objective of controlling rise in prices of essential commodities. In the course of 44 years of operations, Supplyco has expanded into many other areas in retail as a public sector enterprise. Supplyco now has a considerable presence in Kerala’s retail market owing to two factors viz; selling food commodities at subsidized prices and having a large number of retail outlets across Kerala. Yet we hear reports of steep rise in the prices of food commodities and food grains shortage in Kerala. 1 This warrants a study into the effectiveness of Supplyco’s operations in achieving its objective. This paper analyses whether Supplyco as an institution is effective in controlling the rise in prices of essential commodities. The paper also studies whether the activities undertaken by Supplyco are apposite to its stated objective of controlling rise in prices. The financial performance analysis covers finance management capabilities of Supplyco which is one of the largest loss making public sector enterprises in Kerala.